PENGARUH MASSAGE EFFLEURAGE TERHADAP PENGURANGAN NYERI PADA IBU BERSALIN KALA I - Nurmaliza Nurmaliza; Yusmaharani Yusmaharani; Desmariyenti Desmariyenti (LPPM Universitas Abdurrab, 2024)
Pain during labor is a manifestation of contractions (shortening) of the uterine muscles. This contraction causes pain in the waist, stomach area and spreads towards the thighs. The level of labor pain is described by the intensity of pain perceived by the mother during the birth process, if not handled properly, it can increase anxiety or worry to the point of depression and has the effect of increasing the hormone adrenaline, affecting the mother's cardiac output and decreasing uteroplacental perfusion and can cause prolonged labor. One step in reducing pain is with effleurage massage. This research uses a quasi experimental approach method. This study aims to determine the effect of effleurage massage on reducing labor pain in the first stage. The population in this study was all mothers in the first stage of labor at the Pratama Guava Rose Clinic. The sample collection method was purposive sampling with a sample size of 15 people. Data were collected using a pain intensity scale during the pretest before the intervention and posttest after the intervention. The results of research from univariate data showed that the average labor pain before effleurage massage was 6.66 with a standard deviation of 2.02, while the results after effleurage massage were 4.20 with a standard deviation of 1.14. The results of the bivariate research showed that there was an effect of effleurage massage on reducing pain in the first stage of labor with a p-value of 0.000. It is hoped that respondents and health workers can apply the effleurage massage technique during labor to help reduce the pain felt during labor so as to increase maternal comfort.